Food Insecurity Experiences Predict Children's Fruit and Vegetable Consumption in the USA. (19th June 2013) - Howard, Larry L.
Abstract : This research analyses the longitudinal relationships between household food insecurity (very low and low food security) experiences and children's consumption (servings/week) of fruit, green salad, carrots, potatoes, and other types of vegetables. Using a panel of 5, 670 children aged 10–13 years who were first observed in spring 2004 and then again in spring 2007 at age 13–16 years, the main findings are as follows: first, children experiencing low food security consume significantly (P < 0.05 ) more fruit per week. In contrast, children experiencing very low food security consume significantly more carrots and potatoes per week, and estimates based on gender-stratified models indicate that the association is strongest among girls. Second, activity patterns are significantly related to children's dietary patterns; physical exercise is positively associated with fruit, green salad, carrot, and other vegetables consumption, while television watching is positively associated with potato consumption. Overall, the findings suggest that children living in food insecure home environments consume a greater number of servings of fruits and vegetables per week, relative to children living in food secure home environments.